Liberating scholarly writing : the power of personal narrative - Nash, Robert J. (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
This book provides an alternative to the more conventional modes of qualitative and quantitative inquiry currently used in professional training programs, particularly in education. It features a very accessible presentation that combines application, rationale, critique, and inspiration--and is itself an example of this kind of writing.It teaches students how to use personal writing in order to analyze, explicate, and advance their ideas. And it encourages minority students, women, and others to find and express their authentic voices by teaching them to use their own lives as primary resources for their scholarship.
Keywords: Academic writing.; Narrative inquiry (Research method); Education -- Learning Styles.; Competence development.; Educational psychology.; elektronické knihy; electronic books